Parental Monitoring Redefined - Kate Fogarty (EDIS)
FAR0071, a 2-page transcript of the Family Album Radio Program broadcast by Kate Fogarty, provides research-based information on this parenting behavior that helps youths succeed. Includes references. Published by the UF Department of Family Youth and Community Sciences, March 2009.